2017
DOI: 10.1590/0103-6440201701528
|View full text |Cite
|
Sign up to set email alerts
|

Topographic and Chemical Analysis of Reciprocating and Rotary Instruments Surface after Continuous Use

Abstract: This study aimed at evaluating the changes in surface characteristics and NiTi content of reciprocating and rotary instruments after continuous use. Thirty brand-new instruments were assigned to 3 groups (n=10): PNX1 Group -ProTaper Next system -instrument X1; PNX2 Group -ProTaper Next system -instrument X2 and WO Group -WaveOne system -Primary instrument 25.08. The instruments were used to prepare 60 simulated root canals. Analysis of surface characteristics by scanning electron microscopy (SEM) and chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
4
0
2
Order By: Relevance
“…However, these defects were seen in unused instruments, demonstrating that such defects were the result of the manufacturing process. These findings are corroborated by other authors, who also observed these characteristics in unused instruments [15,[21][22][23][24]26]. The difference in defects between unused instruments can be explained by their surface treatment, since One Shape NG files exhibited smooth surface or slight machining marks and the WaveOne files only features of the electropolishing procedures [27].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, these defects were seen in unused instruments, demonstrating that such defects were the result of the manufacturing process. These findings are corroborated by other authors, who also observed these characteristics in unused instruments [15,[21][22][23][24]26]. The difference in defects between unused instruments can be explained by their surface treatment, since One Shape NG files exhibited smooth surface or slight machining marks and the WaveOne files only features of the electropolishing procedures [27].…”
Section: Discussionsupporting
confidence: 80%
“…Although the disruption of cutting edges was present in unused WaveOne files, this defect increased from the sixth usea finding also corroborated by Pirani and coauthors [21], who also found such a disruption in this system according to the number of use. For some authors, the irregular edges found in unused WaveOne files were thought to be a defect [22,23]. However, Pirani and coauthors [21] and our study showed that these cutting edges actually resemble a wave-curl present in these instruments and therefore they should not be considered a defect.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Microcavities and pits (Figure 4h) after use may be associated with the loss of nickel and titanium atoms (Otsuka & Ren, 2005). Grooves (Figure 4g) were observed on the surface of the instrument after preparation, which might function as points of stress concentration, leading to premature failure (Bastos et al, 2017). Microcracks (Figure 4i) develop on the area of spiral distortion, which may have been caused by tensile and torsional overloading (Sattapan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common causes of tool damage is cyclic fatigue [ 4 , 5 , 6 , 7 , 8 ]. It has been found that the fatigue life is affected by many factors, the most important of which are the shape of the tool cross-section, type and quality of tool production, size and length of the tool, and tool movement in the root canal [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Mechanical surface treatment is among the most frequently used methods of surface treatment of NiTi alloys and includes the processes of grinding, sandblasting, and polishing [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%